Analysis and prediction of condylar resorption following orthognathic surgery - Pieter-Jan Verhelst; Sigrid Janssens; Harold Matthews; Giacomo Begnoni; Peter Claes; Eman Shaheen; Hilde Peeters; Constantinus Politis; Reinhilde Jacobs (Scientific Reports)
Abstract Condylar resorption is a feared complication of orthognathic surgery. This study investigated condylar resorption in a cohort of 200 patients This allowed for a powerful update on incidence and risk factors. 9.5% of patients developed resorption. These patients had on average, 17% volume loss with 3.9 mm ramal height loss and 3.1 mm posterior mandibular displacement. 2% of patients had bilateral resorption. Univariable analysis identified a younger age, a bimaxillary + genioplasty procedure, larger mandibular advancements, upward movements of the distal segment, a higher counterclockwise pitch of the distal segment, smaller preoperative condylar volumes and a higher anterior/posterior lower facial height ratio as risk factors on a patient level. Univariable analysis on a condylar level also identified compressive movements of the ramus and a higher mandibular plane angle as risk factors. Using machine learning for the multivariable analysis, the amount of mandibular advancement was the most important predictor for condylar resorption. There were no differences in preoperative mandibular, ramal or condylar shape between patients with or without resorption. These findings suggest condylar resorption may be more common than thought. Identifying risk factors allows surgical plans to be adjusted to reduce the likelihood of resorption, and patients can be more selectively screened postoperatively.